An overview of the potential impacts of atrazine in aquatic environments: Perspectives for tailored solutions based on nanotechnology - Albuquerque, Felícia Pereira de; Oliveira, Jhones Luiz de [UNESP]; Moschini-Carlos, Viviane [UNESP]; Fraceto, Leonardo Fernandes (Elsevier, 2020)
Atrazine is a pre- and post-emergence herbicide used to control weeds in many crops. It was introduced in the late 1950s, but its use has been controversial because of its high potential for environmental contamination. In agriculture, the implementation of sustainable practices can help in reducing the adverse effects atrazine. This review addresses aspects related to the impacts of atrazine in the environment, with focus on its effects on aquatic species, as well as the potential use of nanoencapsulation to decrease the impacts of atrazine. The application of atrazine leads to its dispersal beyond the immediate area, with possible contamination of soils, sediments, plantations, pastures, public supply reservoirs, groundwater, streams, lakes, rivers, seas, and even glaciers. In aquatic ecosystems, atrazine can alter the biota, consequently interfering in the food chains of many species, including benthic organisms. Nanoformulations loaded with atrazine have been developed as a way to reduce the adverse impacts of this herbicide in aquatic and terrestrial ecosystems. Ecotoxicological bioassays have shown that this nanoformulations can improve the targeted delivery of the active ingredient, resulting in decreased dosages to obtain the same effects as conventional formulations. However, more detailed analyses of the ecotoxicological potential of atrazine-based nanoherbicides need to be performed with representative species of different ecosystems.
Keywords: Agrochemical; Aquatic organism; Ecotoxicity; Nanotechnology; Triazinic herbicide